The Influence of Public Health Faculty on College and University Plans During the COVID-19 Pandemic - Johnson, David; Cahill, Meredith; Choate, Sara; Roelfs, David; Walsh, Sarah E. (Frontiers in Public Health, 2022)
The purpose of this study was to explore whether the institutional presence of public health expertise within colleges and universities was associated with operational plans for the fall semester of 2020. Using cross-sectional data collected by the College Crisis Initiative of Davidson College, six levels of instructional modalities (ranked from least to most restrictive) were compared between Council on Education of Public Health (CEPH)-accredited and non-CEPH-accredited 4-year institutions. Institutions with CEPH-accredited schools and programs were more likely to select some restrictive teaching modalities: 63.8% more likely to use hybrid/hyflex or more restrictive and 66.9% more likely to be primarily online (with some in person) or more restrictive. However, having CEPH-accredited programs did not push institutions to the most restrictive modalities. COVID-19 cases in county, enrollment, and political affiliation of the state governor were also found to be associated with instructional modality selection. While any ecological study has certain limitations, this study suggests that college and university fall plans may have been influenced by the presence of CEPH-accredited schools and programs of public health, and/or the input of their faculty. The influence of relevant faculty expertise on institutional decision-making can help inform college and university responses to future crises.